Analisis Hubungan Beban Kerja Fisik Dengan Kelelahan Kerja Penambang Belerang PT. X Banyuwangi - Nadia Firdausi Taurizanti; Abdul Rohim Tualeka (Universitas Airlangga, 2024)
Background: Indonesia is a country with abundant natural resources, one of which is the potential for sulfur in Banyuwangi Regency. This natural potential is managed by PT. X Banyuwangi with the number of workers reaching 249 sulfur miners in the area. Excessive physical workload was found in the mining operational process in the Mount Ijen crater, resulting in a high potential for work fatigue which could lead to work accidents in this business sector. Objective: This study aims to examine the relationship between age, length of service and physical workload with work fatigue of sulfur miners of PT. X Banyuwangi. Method: The research method used is quantitative observational with data analysis using Spearman correlation and correlation coefficient values. Results: The results of the study showed that there was a relationship between age and physical workload and work fatigue of sulfur miners of PT. X Banyuwangi. Apart from that, there is no relationship between work period and work fatigue of sulfur miners of PT. X Banyuwangi. Conclusion: Overall, it can be concluded that age and physical workload are related to work fatigue, while work experience is not related to work fatigue. The recommendations that can be implemented are implementing standard operational procedures in the process of transporting sulfur mining products which is carried out over a distance of 3 km, providing a shift system that allows miners to have working hours in accordance with Indonesian regulations, and providing physical workload limits in the manual handling process. which was carried out in the process of transporting sulfur mining products in the crater area of